2017
DOI: 10.3389/fnagi.2017.00429
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cognitive Reserve and Math Abilities

Abstract: Cognitive Reserve is the capital of knowledge and experiences that an individual acquires over their life-span. Cognitive Reserve is strictly related to Brain Reserve, which is the ability of the brain to cope with damage. These two concepts could explain many phenomena such as the modality of onset in dementia or the different degree of impairment in cognitive abilities in aging. The aim of this study is to verify the effect of Cognitive Reserve, as measured by a questionnaire, on a variety of numerical abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
7
26
0
Order By: Relevance
“…It is likely that individuals were not relying so much on the use of working memory while facing creative tasks. This result is coherent to some extent with the results from Arcara et al ( 2017 ), who reported that a general CR index did not predict abstract math ability. Even if the Digit Span test is not a math test per se , it requires the activation of neural networks related to mathematical thinking, together with working memory (Raghubar et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is likely that individuals were not relying so much on the use of working memory while facing creative tasks. This result is coherent to some extent with the results from Arcara et al ( 2017 ), who reported that a general CR index did not predict abstract math ability. Even if the Digit Span test is not a math test per se , it requires the activation of neural networks related to mathematical thinking, together with working memory (Raghubar et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, studies reporting a role of the DLPFC in moderating CR are particularly relevant to our investigation. Roldán-Tapia et al ( 2012 ) and Arcara et al ( 2017 ) focused on the relationships between the CR and several cognitive and executive functions. Results highlighted that CR levels (mainly education in Arcara and colleagues' study) contribute significantly to the performance in tasks that refer back to functions mainly related to the dorsolateral prefrontal area.…”
Section: Introductionmentioning
confidence: 99%
“… Cabral et al (2016) found a relation between CR and EFs; however, CR was operationalized only with measures of education (years of education, school failure, school attendance), or strictly related to it (reading books, newspapers and number of languages spoken). When using a more complex CR questionnaire, correlations with EFs or related functions sometimes fail to emerge ( Puccioni and Vallesi, 2012b ; Léon et al, 2014 ; Arcara et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another research question is to evaluate whether different cognitive processes are diversely sensitive to CR. In fact, it seems that the beneficial effects of high CR do not necessarily help performance in all cognitive tasks; for example, math performance has been shown to be independent from the level of CR in older adults from 65 years old (Arcara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%